The usage and weight of backpacks are associated with shoulder pain complaints among elementary students - Aisyah Syahidah Ath-Thahirah; Anak Agung Gede Eka Septian Utama; Agung Wiwiek Indrayani; Gede Parta Kinandana (Physical Therapy Journal of Indonesia, 2024)
Background: In recent years, backpack use has drastically increased, especially among elementary school students. This has led to an increase in musculoskeletal complaints, such as shoulder pain, due to the duration of use and the weight of the backpacks. This study investigated the correlation between the duration of use and the weight of backpacks on shoulder pain complaints in grades IV-VI elementary school students. Methods: This study employed an analytical observational research design with a cross-sectional study design. The inclusion criteria for this study were students aged 10-12 years old, using backpacks with shoulder straps, walking to and from school. In contrast, the exclusion criteria were injuries in the shoulder region. The sampling technique employed in this study was probability sampling, specifically simple random sampling. The research was conducted at Islamic Elementary School 1 and 2 in Karangasem, Bali. The sample size was calculated using the Lameshow formula, resulting in 106 samples. Results: Based on bivariate analysis using Pearson’s Correlation Coefficient (r), the p-value obtained was 0.000 (p< 0.05) for both independent variables, with correlation coefficients of r = 0.570 for the duration of use variable and r = 0.709 for the backpack weight variable. Based on multivariate analysis using Multiple Linear Regression in the F-test or simultaneous test, the p-value obtained was 0.000 (p < 0.05). Conclusion: Based on the research results, it can be concluded that there was a correlation between the duration of use and the backpack's weight on shoulder pain complaints, both partially and simultaneously.